Anaerobic Digestion - Cynthia Carliell-Marquet (Frontiers Research Topics, 2018)
Anaerobic digestion (AD) is a naturally-occurring biological process in soils, sediments, ruminants, and several other anoxic environments, that cycles carbon and other nutrients, and converts organic matter into a methane-rich gas. As a biotechnology, AD is now well-established for the treatment of the organic fraction of various waste materials, including wastewaters, but is also increasingly applied for an expanding range of organic feedstocks suitable for biological conversion to biogas. AD applications are classified in various ways, including on the basis of bioreactor design; and operating parameters, such as retention time, temperature, pH, total solids (TS) and volatile solids (VS) contents, and biodegradability of substrates. AD is an attractive bioenergy and waste / wastewater treatment technology. The advantages of AD for waste treatment include: production of a useable fuel (biogas/methane); possibility of high organic loading; reduced carbon footprint; and suitability for integration into a wide variety of process configurations and scales. Specifically, two important, and developing, applications exemplify the potential of AD technologies: (1) the integration of AD as the basis of the core technologies underpinning municipal wastewater, and sewage, treatment, to displace less sustainable, and more energy-intensive, aerobic biological treatment systems in urban water infrastructures; and (2) technical innovations for higher-rate conversions of high-solids wastestreams, and feedstocks, for the production of energy carriers (i.e. methane-biogas, but possibly also biohydrogen) and other industrially-relevant intermediates, such as organic acids. Internationally, the research effort to maximize AD biogas yield has increased ten-fold over the past decade. Depending on the feedstocks, bioreactor design and process parameters, fundamental and applied knowledge are still required to improve conversion rates and biogas yields. This Research Topic cover aspects related to AD processes, such as the effect of feedstock composition, as well as the effect of feedstock pre-treatment, bioreactor design and operating modes, on process efficiency; microbial community dynamics and systems biology; influence of macro- and micro-nutrient concentrations and availability; process control; upgrading and calibration of anaerobic digestion models (e.g. ADM1) considering the biochemical routes as well as the hydrodynamics in such ecosystems; and novel approaches to process monitoring, such as the development, and application, of novel, and rapid diagnostic assays, including those based on molecular microbiology. Detailed full-scale application studies were also particularly welcomed.